Adhesions and Healing of Intestinal Anastomoses: The Effect of Anti-Adhesion Barriers. (June 2016) - Ntourakis, Dimitrios; Katsimpoulas, Michail; Tanoglidi, Anna; Barbatis, Calypso; Karayannacos, Panayotis E.; Sergentanis, Theodoros N.; Kostomitsopoulos, Nikolaos; Machairas, Anastasios
Background . Postoperative adhesions are the result of aberrant peritoneal healing. As they are the leading cause of postoperative bowel obstruction, anti-adherence barriers are advocated for their prevention. This study looks into the effect of these biomaterials on the healing of intestinal anastomoses. Materials and Methods . Thirty-three New Zealand White rabbits underwent laparotomy, transection of the terminal ileum, and creation of an end-to-end anastomosis. Animals were randomized into 3 groups: the Control group (n = 11); the Icodextrin group, receiving icodextrin 4% intraperitonealy (n = 11); and the HA/CMC group, having the anastomosis wrapped with a hyaluronic acid/carboxymethylcellulose film (n = 11). All animals were sacrificed on the seventh postoperative day. Macroscopic adhesions were graded and anastomotic strength was tested by the burst pressure. Histological healing was assessed in a semiquantitative way for the presence of ulceration, reepithelization, granulation tissue, inflammation, eosinophilic infiltration, serosal inflammation, and microscopic adhesions. Univariate and multivariate analysis was used. Results are given as medians with interquartile range. Results . The median adhesion scores were the following: Control 1 (0-3), Icodextrin 0 (0-1), HA/CMC 0 (0-0), P = .017. The burst pressure did not differ between the groups; however, all except one bowel segments tested burst away from the anastomosis. The macroscopic and histological anastomotic healing was comparable in all 3 groups. A poor histological anastomotic healing score was associated with a higher adhesion grade (odds ratio = 1.92; 95% confidence interval = 1.06-3.47; P = .032). Conclusion . Adhesion formation was inhibited by the materials tested without direct detrimental effects on anastomotic healing. Poor anastomotic healing provokes adhesions even in the presence of anti-adhesion barriers.